RTL Modelling for the Cipher Blcok Chaining Mode (Cbc) for Data Security - Meenakshi R. K; A. Arivazhagan (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
The demand of satellite communication, the security algorithms are to be designed in the board. The information from the satellite to the ground is required the data security with the cryptographic algorithms. Advanced encryption standard (AES) is one of the promising cryptographic algorithms for the terrestrial communication. In this paper, the encryption and decryption is mainly focused on the cipher block chaining (CBC) mode for achieving the high secured data transmission. For efficient data transmission, the AES algorithm is implemented by using CBC mode. The proposed work is designed by using RTL modeling and also the minimum numbers of logical elements are used for implementation.